Effect of specific resistance training on overarm throwing performance - Ettema, G.; Glosen, T.; van den Tillaar, R. (International Journal of Sports Physiology and Performance, 2008)
The main purpose of this study was to compare the effect of a specific resistance training program (throwing movement with a pulley device) with the effect of regular training (throwing with regular balls) on overarm throwing velocity under various conditions. Methods: The training forms were matched for total training load, ie, impulse generated on the ball or pulley device. Both training groups (resistance training n = 7 and regular training n = 6) consisted of women team handball players, and trained 3 times per week for 8 weeks, according to an assigned training program alongside their normal handball training. Results: An increase in throwing velocity with normal balls after the training period was observed for both groups (P = .014), as well as throwing with heavier balls and throwing like actions in the pulley device. Although the regular training group seemed to improve more (6.1%) in throwing velocity with normal balls than the resistance training group (1.4%), this difference was not statistically significant. Conclusions: These findings indicate that resistance training does not surpass standard throwing training in improvement of overarm throwing velocity.